Bicyclol Alleviates Atherosclerosis by Manipulating Gut Microbiota (Small 9/2022). Issue 9 (3rd March 2022) - Li, Xiao‐Lin; Cui, Jin‐Jin; Zheng, Wen‐Sheng; Zhang, Jin‐Lan; Li, Rui; Ma, Xiao‐Lei; Lin, Miao; Guo, Hui‐Hui; Li, Cong; Yu, Xiao‐You; Du, Peng; Zhao, Li‐Min; et al.
Abstract : Atherosclerosis Treatment Herb derived drugs modulate gut microbiome homeostasis and gut‐generated bio‐metabolites. In article number 2105021, Jian‐Dong Jiang, Yongsheng Che, Lu‐Lu Wang, and co‐workers modify the immune cell dynamics and liver function using herb‐derived bicyclol, leading to improved chronic inflammation and cholesterol metabolism. The endothelial activation and cholesterol ester accumulation in the aortic arch are ameliorated causing less plaque onset.